Optimasi Pemilihan Smartphone Gaming Terbaik di Kelas Menengah Menggunakan Metode Simple Additive Weighting (SAW) Berbasis Preferensi Konsumen - Samantha Arta Sinuhaji; Sandy Hardiansyah; Candra Harapan Simanjuntak; Yulita Santa Nova Girsang; Victor Asido Elyakim P (JUMINTAL: Jurnal Manajemen Informatika dan Bisnis Digital, 2024)
The selection of middle-class gaming smartphones is a challenge for consumers because there are many choices with varying specifications. This research aims to help consumers make the best choice by applying the Simple Additive Weighting (SAW) method. This method is used to provide recommendations based on a number of key criteria, such as processor performance, RAM capacity, screen quality, battery life, and price. The initial step in this research is to identify the problem, which is the selection of the best gaming smartphone in the middle-class category. Next, alternatives and relevant criteria were determined, followed by data collection through a questionnaire involving 78 respondents. The data obtained was analyzed using the SAW method to determine the importance weight of each criterion and the overall ranking of each alternative. The analysis results show that Infinix ranks highest as the best choice based on the aggregate score obtained for each criterion. The SAW method allows decision making to be more systematic and objective by considering predetermined weights. The conclusion of this study confirms that a SAW-based approach can assist consumers in choosing a gaming smartphone that suits their needs and preferences. This study also provides insights for manufacturers in devising more effective marketing strategies.